INTEGRATED ASSESSMENT AND MULTISCALE MAPPING OF POPULATION INCIDENCE WITH MALIGNANT NEOPLASMS - Belousov, Станислав Константинович; Vatlina, Тамара Валентиновна; Tikunov, Владимир Сергеевич (Geographical Bulletin, 2023)
This article presents a method for an integral assessment of the incidence of malignant neoplasms in population taking into account their localization in the human body. The method is based on multidimensional aggregation of malignant tumor incidence rates at various scale levels. For a multiscale assessment, three levels of research were selected: countries of the world, federal districts of Russia, and regions of Russia. Incidence data for the countries of the world were obtained from the World Health Organization’s project Global Cancer Observatory. For Russia, the initial data were taken from the yearbook Malignant Neoplasms in Russia prepared by the P.A. Herzen Moscow Research Institute of Oncology. We compiled integral indices of the malignant neoplasms incidence for men and women as well as corresponding maps for various scale levels. This study is the first to implement, on the basis of an integrated approach, a model of epidemiological analysis of oncological morbidity at different spatial levels. The study showed that regional differentiation of the incidence index of malignant neoplasms in men and women requires different approaches.